Apical root canal transportation of different pathfinding systems and their effects on shaping ability of ProTaper Next - Türker, Sevinç-Aktemur (J Clin Exp Dent, 2015)
BACKGROUND: This study aimed to compare glide path preparation of different pathfinding systems and their effects on the apical transportation of ProTaper Next (Dentsply Maillefer, Ballaigues, Switzerland) in mesial root canals of extracted human mandibular molars, using digital subtraction radiography. MATERIAL AND METHODS: The mesial canals of 40 mandibular first molars (with curvature angles between 25° and 35°) were selected for this study. The specimens were divided randomly into 4 groups with 10 canals each. Glide paths were created in group 1 with #10, #15 and #20 K-type (Dentsply Maillefer, Ballaigues, Switzerland) stainless steel manual files; in group 2 with Path-File (Dentsply Maillefer) #1, #2, and #3 and in group 3 with #16 ProGlider (Dentsply Maillefer) rotary instruments; in group 4 no glide paths were created. All canals were instrumented up to ProTaper Next X2 to the working length. A double digital radiograph technique was used, pre and post-instrumentation, to assess whether apical transportation and/or aberration in root canal morphology occurred. Instrument failures were also recorded. The data were analyzed statistically using ANOVA and Tukey tests (p<0.05). RESULTS: No significant differences were found among groups regarding apical transportation (p>0.05). Two ProTaper Next instruments failed in-group 4. CONCLUSIONS: Within the parameters of this study, there was no difference between the performance of path-finding files and ProTaper Next system maintained root canal curvature well and was safe to use either with path-finding files or alone. Key words:Glide path, PathFile, ProGlider, ProTaper Next, transportation.